Simulating Distributional Impacts of Macro-dynamics : Theory and Practical Applications - Olivieri, Sergio (World Bank Group, Washington, DC, 2014)
Simulating Distributional Impacts of Macro-dynamics: Theory and Practical Applications is a comprehensive guide for analyzing and understanding the effects of macroeconomic shocks on income and consumption distribution, as well as using the ADePT Simulation Module. Since real-time micro data is rarely available, the Simulation Module (part of the ADePT economic analysis software) takes advantage of historical household surveys to estimate how current or proposed macro changes might impact household and individuals welfare.